Odpowiedź :
Odpowiedź:
a. -3*-0,25*-2=-1,5
b. 3-4+1,5=0,5
c. 2*4=8
d. 15*-1=-15
e. -2^2=4
Odpowiedź:
Szczegółowe wyjaśnienie:
f)(-4a-b)(b-a)-4a²+b²=-4ab+4a²-b²+ab-4a²+b²=-4ab
teraz podstawiamy -4×(-0,25)×(-2)=-2
g)2x³-5x-2x(x²-1)+3y=2x³-5x-2x³+2x+3y=-3x+3y
podstawiamy -3×(-1)+3×0,5=3+1,5=4,5
h) a²-ab-ab+b²+2ab-(a²+ab-ab-b²)=a²+b²-a²+b²=2b²
podstawiamy 2×(-2)²=2×4=8
i) (3x-15)(x+5)-3x²+15x+75=3x²+15x-15x-75-3x²+15x+75=15x
podstawiamy 15×(-1)=-15
j) -(b²-16a²)-16a²+2b²=-b²+16a²-16a²+2b²=b²
podstawiamy (-2)²=4